2002
DOI: 10.1139/x02-057
|View full text |Cite
|
Sign up to set email alerts
|

Songbird abundance in clear-cut and burned stands: a comparison of natural disturbance and forest management

Abstract: To evaluate the efficacy of forest management to emulate natural disturbance, we compared bird abundances among burned and clear-cut, former black spruce (Picea mariana (Mill.) BSP) sites, after 5, 14, and 27 years of succession. Total bird density was lower in clear-cut sites resulting from fewer hermit thrushes, yellow warblers, Swainson's thrushes, and fox sparrows. Hermit thrushes were positively correlated with snag density while yellow warblers and Swainson's thrushes were positively associated with deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 17 publications
4
38
0
Order By: Relevance
“…Our findings are also consistent with other evidence that vegetation successional patterns affect bird community composition after disturbance (e.g., Schulte and Niemi 1998, Hobson and Schieck 1999, Thompson et al 1999, McRae et al 2001, Simon et al 2002. Community-level estimates were consistent with the idea that species richness in temperate forests is generally greater in younger successional communities, because recently disturbed ecosystems typically have greater nutrient availability and energy exchange than older ecosystems (Gower et al 1996).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our findings are also consistent with other evidence that vegetation successional patterns affect bird community composition after disturbance (e.g., Schulte and Niemi 1998, Hobson and Schieck 1999, Thompson et al 1999, McRae et al 2001, Simon et al 2002. Community-level estimates were consistent with the idea that species richness in temperate forests is generally greater in younger successional communities, because recently disturbed ecosystems typically have greater nutrient availability and energy exchange than older ecosystems (Gower et al 1996).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies suggest that some bird species found in naturally disturbed forest stands are significantly less abundant in postharvest stands of similar types and ages, especially in the earliest successional stages but also several decades after harvest (e.g., Schulte and Niemi 1998, Hannon 1999, Imbeau et al 1999, Simon et al 2002. However, others find little difference for most species (e.g., Lemelin et al 2007, Börger and Nudds 2014, Rempel et al 2016.…”
Section: Introductionmentioning
confidence: 99%
“…This manipulation of forest structure alters nesting habitat, food availability and predator abundance relative to unperturbed forests [8]. Much attention has been paid to the response and recovery of populations after burning, clearcuts, or thinning [9][10][11][12], with a focus on community richness and species density [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the water table can move up in the five years following clear-cutting (Pothier et al 2003), creating favorable mesic conditions. WIWA have been reported as breeding in recent clear-cuts in Québec and Labrador (Crête et al 1995, Imbeau et al 1999, Simon et al 2002. Clear-cuts may be suboptimal for the species, however.…”
Section: Introductionmentioning
confidence: 99%